CHEMICALS AND HAZARDOUS WASTES GENERATED BY SHIPYARD PRODUCTION AND THEIR EFFECTS ON HUMAN HEALTH AT WORKPLACE - Celebi, Ugur Bugra; Akanlar, Fuat Tolga; Vardar, Nurten (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2009)
Shipbuilding industry is listed as heavy industry due to the use of raw materials and production processes, which mostly have an impact on human health and environment as contaminants. Various types of solid, liquid and gaseous form of wastes are known as the outcome of shipbuilding and ship repair processes. These contaminants may affect water, air and soil unless preventive actions are considered. The effect of these contaminants on workers health is as important as the environmental effect. In this study, some common production processes such as blasting, painting, welding, and fiberglass production processes are examined. The effect of the contaminants and wastes of these processes on workers health is investigated in detail. The importance of minimization or reuse of these wastes and contaminants without affecting human health or environment comes into prominence. In recent years, the most important step to avoid contamination is not to produce contaminants. The first aim on this route is to minimize the wastes and pollutants outcoming from the production processes. In addition to this, new alternative methods not causing economic cost increase should be developed.
Keywords: Shipyard wastes; Shipyard worker; Hazardous waste; Occupational health; Production chemicals; EXPOSURE; FUMES; Environmental Sciences & Ecology